PENINGKATAN KEMAMPUAN BERBICARA SISWA DENGAN MENGGUNAKAN TEKNIK BRAINSTORMING DI SEKOLAH DASAR - -, ZAHARNI (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
AbstractThe purpose of this study was to describe the implementation and improvement of student’s speaking skill. Data collection is done by observation through the observation sheet aspect and aspect of student teacher. The subject of the research was the teacher and the students of class 6 SDN SUNGAI Geringging Kabupaten Padang Pariaman. THE research in cycle I 73,91, II INCREASED TO 84,46. This shows using brainstorming techniques can improve students speaking skills Kata kunci : brainstorming, hasil belajar, keterampilan berbicara